Battle for the Zephyr badge ; All fired up - Johnson, Jennifer L. (New York : Scholastic Inc., 2021)
"Trouble seems to following Ash and his team around! A Quagsire takes the GS Ball. A young boy at a Pokemon. Trainer school tries to catch Pikachu. And Team Rocket is up to their usual troublesome tricks. How will Ash ever get it together to go for his first Johto League badge?"--Back cover.
Charizard can only get stronger if it leaves Ash -- forever. But that means Ash has no Fire-type Pokemon at all. Have his dreams of becoming a Pokemon Master gone up in flames?
Texts bound back-to-back and inverted.
For children.
Accelerated Reader
Keywords: Pokemon (Fictitious characters) -- Juvenile fiction; Animal training -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Upside-down books